Novel link between myeloid-specific adenosine deaminase 2 and CXCL10-CXCR3 axis in infectious ARDS - Tiwari-Heckler, Shilpa; Pita-Juarez, Yered; Vierbaum, Lisa; Michl, Patrick; Vlachos, Ioannis S.; Merle, Uta; Jiang, Z. Gordon (International journal of molecular sciences, 2025)
Acute respiratory distress syndrome (ARDS) is a severe complication of lung injury characterized by hyperinflammation and fibrosis.